Flebologické problémy a diabetes - Kaspar, S (Vnitrni lekarstvi, 2010)
Patients with trophic ulcers of lower extremities are relatively frequently diagnosed with diabetes mellitus with venous aetiology being the cause of these defects in up to 70% of patients. Chronic venous insufficiency most frequently results from primary venous insufficiency (mostly lower limb varices) or occurs secondarily as a result of deep vein thrombosis. Lower limb varices are common in human population; they affect 20-25% of women and 10-15% of men, and the incidence increases with age. With respect to radicality of treatment approaches, surgical management is unequivocally considered as the most effective. Apart from the traditional open surgery, clinical practice of the recent years has seen the advance of mini-invasive endovascular methods to treat varices of the main (stem) veins--radiofrequency and laser thermocoagulation. The main principle behind radiofrequency ablation is thermocoagulation of insufficient saphenous vein by bipolar radiofrequency current; endovenous laser uses, for the same purpose, energy of a beam of light. Both methods inactivate the insufficient veins while leaving them in the patient body. Thermal damage of the pathological venous wall leads to contraction and obliteration of the vein and, gradually, to its full resorption. Apart from minimizing recurrence, the technique is also valuable with respect to its cosmetic effect and gentleness of the procedure, allowing fast return to full activity. Studies comparing endovascular interventions with the traditional surgeries confirmed that radiofrequency or laser techniques are safe and well tolerated with the outcomes fully comparable to open surgery in its modern form.
Keywords: žilní insuficience; Diabetic Angiopathies; diabetické angiopatie; Minimally Invasive Surgical Procedures; varixy; miniinvazivní chirurgické výkony; lidé; Varicose Veins; Venous Insufficiency; Humans